Highly-Sensitive Polymer Optical Fiber SPR Sensor for Fast Immunoassay - Ying Wang; Xing Rao; Xun Wu; George Y. Chen; Changrui Liao; Mateusz Jakub Smietana; Yiping Wang (Photonic Sensors)
Abstract A new type of human immunoglobulin G (IgG) sensors based on the surface plasmon resonance (SPR) in the low refractive index (RI) plastic optical fiber (POF) and an antibody immobilization method is presented. A 50-nm-thick gold film was formed on the polished D-shaped fiber surface by magnetron sputtering. The RI response of the POF sensor is 30 049.61 nm/RIU, which is 26.5 times higher than that of single mode fiber (SMF) SPR sensors. The proposed SPR biosensor can be developed by simple and rapid modification of the gold film with 11-mercapto undecanoic acid (MUA). Upon immobilization of the goat anti-human IgG antibody, the resonance wavelength shifts by 11.2 nm. The sensor can be used to specifically detect and quantify the human IgG at concentrations down to 245.4 ng/mL with the sensitivity of 1.327 7 nm per µg/mL, which offers an enhancement of 12.5-fold compared to that of the conventional SMF based SPR sensors. The proposed device may find the potential applications in the case of use at the point of care.